GREEN CHEMISTRY AND ITS IMPORTANCE IN OUR LIFE - D.A.Karimova; Kurbanova F.Sh (Western European Studies, 2025)
Green chemistry is an important part of modern chemistry, aimed at developing chemical substances and processes in a way that does not harm human health and the environment. Its twelve principles were developed by chemists, guiding the design of chemical technologies. They help to develop practical applications, such as Petretec technology. As we know, petroleum products are considered resources that do not comply with the principles of green chemistry, while PET (polyethylene terephthalate) may partially comply with the principles of green chemistry, but its production processes require recycling and compliance with the principles of green chemistry to reduce their impact on the environment.
Keywords: chemistry; environment; applications; recycling